How to Avoid Primary Nonresponders to Infliximab in Crohn's Disease. Issue 11 (November 2017) - Chiba, Mitsuro; Tsuji, Tsuyotoshi; Nakane, Kunio; Ishii, Hajime; Komatsu, Masafumi
Abstract : Article first published online 6 October 2017.